Energy and Resource Efficiency in Aluminium Die Casting - Heinemann, Tim.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This monograph provides a field-proven approach to analyze industrial production with a cross-company scope as well as regarding all hierarchical system levels of manufacturing enterprises. The book exemplifies this approach in the context of aluminum  die casting, and presents a set of measures which allow a 30 percent energy reduction along the value chain. The target audience primarily comprises researchers and experts in the field but the book may also be beneficial for graduate students.
Introduction -- Aluminium die casting and its environmental aspects -- Existing approaches -- Multi-level multi-scale framework for enhancing energy and resource efficiency in production -- Multi-level multi-scale framework for enhancing energy and resource efficiency in aluminium die casting -- Summary and Outlook.
Keywords: Energy policy; Energy and state; Manufactures; Environmental monitoring; Metals; Energy Policy, Economics and Management; Machines, Tools, Processes; Environmental Monitoring; Metals and Alloys